The Trinity Model in The Family of Educators: Reflections on Love and Unity - Theresia Martini (Fakultas Teologi, Universitas Sanata Dharma, 2025)
The family serves as the primary and foundational place of education for Christians. It plays a crucial role in shaping values and nurturing relationships with God. This discussion focuses on the concept of the Triune God, which serves as a model for the family life of educators. Using the Interpretative Phenomenological Analysis (IPA) approach, the researcher aims to explore various aspects of educators' family life associated with the teachings of the Council of Nicaea. Just as the Father and the Son exist in the fellowship of the Holy Spirit, families are also called to embody love, share, and cultivate close relationships. Additionally, the ideals of unity in diversity and self-giving reflect the nature of the Trinity within the family. This study seeks to illustrate how the family, regarded as a